Effectiveness of Buzz Group Technique in the Teaching of Reading At SMP Negeri 10 Kendari - Budikafa, Fandi Ardiansyah; Sidu Marafat, La Ode; Lio, Asrun (Journal of Language Education and Educational Technology (JLEET), 2017)
Since there have been many different models of reading instruction put forth, yet few of these methods take into account the importance of motivation. In fact, attempts at improving reading comprehension using Buzz Group technique seem to focus too heavily on the mechanics of reading without delving into the emotional or psychological aspects especially motivation. The purpose of this research is to identify the difference in students’ reading comprehension despite taught by different method. In addition, the research aims to identify the difference in reading comprehension of highly motivated and lowly motivated students which are taught using different method. The methods used in this research were Buzz Group technique and Contextual Method. 114 students of Grade VIII at SMPN 10 Kendari participated in completing the questionnaire reflecting their level of motivation and then 57 of them were given the reading comprehension test and the method used for analyzing the results was two-way anova technique. The results obtained showed that the reading comprehension of students who were taught using different method was not significantly different but the teaching method is needed for enhancing students’ reading comprehension by the development of students’ critical thinking provided by Buzz Group technique. Moreover, the reading comprehension of highly motivated students was significantly different from lowly motivated students; this was proved on this research that the higher the motivation, the higher the reading comprehension is. The findings can help to clarify the nature of reading comprehension that despite from taught using right method, it is important if teachers develop and integrate a strong emphasis on reading motivation, and value its effective environment.